Christophe Berteaux : Chemises d'Artistes. (Nancy : [s.n.])
Alsterlind, Mark ; Autard, Georges ; Ben ; Bize, Hervé ; Buraglio, Pierre ; Ducorroy, Joël ; Humair, JDaniel ; Koechlin, Lionel ; Malingrey, Rémi ; Morellet, François ; Pouppeville, denis ; Romain, Hippolyte ; Segui, Antonio
uitgegeven in eigen beheer
Nederlands
boek